Relationship between Interleukin 6 and Estradiol Levels in Obese and Adult Men - Dwipayana, I Made Pande; Semadi, I Made Siswadi; Nugraha, Ida Bagus Aditya; Gotera, Wira; Saraswati, Made Ratna; Suastika, Ketut; Saraswati, Putu Ayu Indah (Berkala Kedokteran, 2025)
Obesity is a chronic disease characterized by a pathophysiological process that causes an increase in adipose tissue mass, leading to an increased risk of morbidity and mortality. Currently, there are many conditions that allow the interaction between environmental factors and genes that lead to various metabolic disease complications, such as diabetes mellitus and heart attack. Health workers are at the forefront of managing obesity and its associated complications. The study was conducted at Ngoerah Hospital from March to October 2024. The target population in this study were adult male medical personnel with and without obesity, working at Ngurah Hospital. The inclusion criteria in this study: male health workers in the environment at Ngoerah Hospital aged 18-45 years and willing to participate in the study by signing informed consent. Exclusion criteria in this study were all male health workers with infectious or inflammatory diseases, and or suffering from malignancies or a history of chemotherapy, and or with the use of hormonal therapy. The sample size of the study was 64 subjects. Data analysis included descriptive statistics, a normality test using the Kolmogorov-Smirnov test, a comparison test using the Mann-Whitney U test, and a correlation test using the Spearman rank correlation. This study was approved by the Research Ethics Commission, approval number 1697/UN14.2.2.VII.14/LT/2024. The results of this study found that IL-6 and estradiol levels in the obese group were higher than the non-obese group, however, the differences were not statistically significant. This may be attributed to the relatively young age of the subjects and the absence of significant inflammation in the early stages of obesity. There was no significant correlation between IL-6 and estradiol in all subjects, obese and non-obese groups.